THE TAX BURDEN, TUNNELLING INCENTIVES, FOREIGN OWNERSHIP AND BONUS MECHANISM ON TRANSFER PRICING - Ananda, Silvia; Sumarna, Alfonsa Dian (Universitas Airlangga, 2025)
Transfer pricing refers to the determination of prices for goods, services, and intangible assets traded between related entities, such as affiliated companies or subsidiaries within a multinational corporation. In its implementation, transfer pricing must adhere to the arm’s length principle. This study analyses the effect of tax burden, tunnelling incentives, foreign ownership, and bonus mechanisms on transfer pricing decisions in oil, gas, coal and supporting sub-sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. The sample in this study was selected using purposive sampling with a total of 93 firm year observation. This study used secondary data obtained from the Indonesia Stock Exchange website, the OSIRIS database, and the companies' official websites. This data is analyzed with panel data regression analysis using the EViews v12 program. The results show that tax burden and tunnelling incentives significantly affect transfer pricing. In contrast, foreign ownership and bonus mechanisms do not substantially affect transfer pricing.